Early Clinical, Biochemical and Radiological Features in Obese and Non-Obese Young Women with Polycystic Ovarian Syndrome: A Comparative Study - Kumar, Naina; Agarwal, Himani (Hormone and Metabolic Research, 2022)
Polycystic ovarian syndrome (PCOS) is a heterogenous condition accounting for serious health complications. The present study was conducted to assess the early clinical, biochemical, and radiological features in obese, non-obese young women with PCOS as compared to non-PCOS women. The study was conducted on 120 young women (18–22 years) with 80 having features of PCOS [40 obese (BMI≥25 kg/m2) and 40 non-obese (BMI<25 kg/m2) PCOS] as cases and 40 without PCOS as controls in a rural tertiary care center of Northern India over one year (2017–2018). After enrolment of cases and control, the anthropometric measurements, early clinical symptoms, and biochemical and ultrasonographic features were compared between the groups. Statistical analysis was done using SPSS software version 22.0 (p-value<0.05). A significant difference in anthropometric measurements were observed between obese and non-obese PCOS cases. Clinical features like acne, acanthosis nigricans, and hirsutism were more prevalent in obese PCOS as compared to non-obese and controls. On ultrasound, PCOS cases had a significantly increased number of peripherally arranged ovarian follicles, and ovarian volume. The LH: FSH ratio was significantly higher in cases as compared to controls. The levels of serum LH (10.04±1.60 vs. 8.93±2.40 mIU/ml) and total testosterone (2.71±0.39 vs. 2.21±0.39 pg/ml) were higher in obese PCOS as compared to non-obese PCOS cases. In conclusion, clinical, biochemical, and radiological features can be used in the early diagnosis of PCOS. Obesity is an independent risk factor for PCOS and is associated with an increased risk of complications.
Keywords: hirsutism; hyperandrogenemia; polycystic ovary syndrome; body weight; FSH